Outage performance analysis of IRS-aided cognitive satellite-terrestrial network - Min LIN; Huaibo GUO; Xiaoyu LIU; Lue HAN; Miaomiao TAN; Lyuxi YANG (Tongxin xuebao)
The outage performance of intelligent reflecting surface (IRS) aided cognitive satellite-terrestrial network was analyzed.Firstly, for the scenario where the point beam was enabled at the satellite to serve the earth station, and the IRS and non-orthogonal multiple access (NOMA) were deployed at the base station to expand the communication range and serve multiple users, respectively, under the condition that cognitive radio technology was employed to enable spectrum sharing between the satellite primary network and the terrestrial secondary network, an optimization problem was established to maximize the average signal-to-noise ratio of terrestrial users.Secondly, a low complexity IRS phase shift design was proposed by using channel state information based on the angle domain, and the phase shift matrix of IRS was obtained.Then, the closed-form expressions of outage probabilities of terrestrial users were derived when users were static and moving, respectively.Furthermore, the asymptotic outage probability formulas at high signal-to-noise ratio were also derived to analyze the system performance.Finally, the correctness of derivation and the influence of main parameters on outage performance were verified by computer simulations.